Simultaneous NOX and CO₂ Reduction for Meeting Future California Air Resources Board Standards Using a Heavy-Duty Diesel Cylinder Deactivation-NVH Strategy - Neely, Gary; Sharp, Chris; Pieczko, Matthew; McCarthy, James E. (SAE International journal of engines, 2020)
Commercial vehicles require continual improvements in order to meet fuel consumption standards, improve diesel aftertreatment (AT) system performance, and optimize vehicle fuel economy. Simultaneous reductions in both CO₂ and NOX emissions will be required to meet the upcoming regulatory targets for both EPA Phase 2 Greenhouse Gas Standards and new Low NOX Standards being proposed by the California Air Resources Board (CARB). In addition, CARB recently proposed a new certification cycle that will require high NOX conversion while vehicles are operating at lower loads than current regulatory cycles require. Cylinder deactivation (CDA) offers a powerful technology lever for meeting these two regulatory targets on commercial diesel engines. There have been numerous works in the past year showing the benefits of diesel CDA for elevating exhaust temperatures during low-load operation where it is normally too cold for AT to function at peak efficiency. At the same time, CO₂ and fuel consumption are reduced through a combination of lower pumping and friction losses and improved thermal efficiency in the cylinders that are still firing. However, CDA has the potential to alter the vehicle vibration, and therefore a strategy must be developed to mitigate these NVH issues while taking advantage of the performance benefits mentioned previously. This article focuses on demonstrating the merits of diesel CDA at low load on a heavy-duty diesel engine in a dynamometer test cell. Results show: 1. An NVH recipe to minimize system vibration when using CDA; 2. Exhaust temperature increase and fuel savings at low load operating modes; 3. Ability to get the AT hot from a cold start using CDA combined with elevated idle speeds; 4. CDA operation over HD FTP and the CARB proposed LLC.